Pengaruh Pola Asuh Pola Pemberian Makan Dan Status Gizi Ibu Saat Hamilterhadap Kejadian Stunting Pada Balita Usia 12-59 Bulan Di Wilayah Kerja Puskesmas Pekan Labuhan Kecamatan Medan Labuhan Kota Medan Tahun 2023 - Marbun, Aghsila Hasma; Badi’ah, Atik; Maimunah, Siti (Lembaga Dongan Dosen, 2024)
The high rate of stunting problems that occur reflects the existence of chronic nutritional problems, influenced by the condition of the mother or prospective mother, during the fetal period and infancy/toddlerhood, including illnesses suffered during the toddler years. Like nutritional problems, they are not only related to health problems, but are also influenced by various other conditions that indirectly affect health. This research aims to determine the influence of parenting patterns, feeding patterns and nutritional status of mothers during pregnancy on the incidence of stunting. In this study, a cross-sectional research design was used. The research population was at the Pekan Labuhan Community Health Center, Medan Labuhan District, Medan City. The collection technique uses purposive sampling. The total sample was 39 people. This statistical test uses multiple logistic regression. Parenting style has a significant influence on the incidence of stunting (P Value 0.004 < 0.05), Diet has a significant influence on the incidence of stunting (P Value 0.021 < 0.05), Nutritional status has a significant influence on the incidence of stunting (P value 0.002 < 0.05). The conclusion of this research is that the most dominant factor influencing the incidence of stunting is nutritional status. It is recommended that health workers develop Posyandu/nutrition cadres to provide education or counseling regarding stunting, nutritional knowledge, maternal parenting and environmental cleanliness.